A Scientific Inquiry on the Estimation of the Phillips Curve in the Baltic Region - Furuoka, F. (Kauno Technologijos Universitetas, 2016)
Many countries in European Union (EU) have suffered from the high unemployment rate due to the Eurozone crisis in the end of the 2000s. However, there is a knowledge gap in this important area of study. Many researchers focused on the Western part of Eurozone or PIGS (Portugal, Italy, Spain and Greece) and there is lack of systematic analysis on the Baltic countries. This paper aims to deal with an important scientific problem in macroeconomics regarding a trade-off relationship between unemployment rates and inflation rates. In other words, the main objective of this paper is to revisit the Phillip curve debate by estimating a new Keynesian Phillips curve (NKPC) in three European Union (EU) member countries in Baltic region, namely Estonia, Latvia and Lithuania for the period of 1995-2013. For the purpose of scientific inquiry, this paper used the generalized method of movements (GMM) approach suggested by Gali and Gertler (1999). The novelty of this study is that it is first in its kind to apply the Gali-Gertler (GG) method to examine scientifically a trade-off relationship between inflation and unemployment in these three EU countries. The empirical analysis revealed some important findings. First and foremost, the empirical findings clearly indicated that inflation dynamics in three EU countries in the Baltic region was largely determined by the forward-looking tendency. This means that numerous firms in the region would have a forward-looking price setting tendency. These firms would pay due attention to the expected level of inflation rate in the future. This is main findings from this empirical analysis. Secondly, the findings also indicated that the inflation dynamics does not seem to be determined by the backward-looking behavior. It means that many firms in the region do not seem to have a backward-looking orientation. Thirdly, the empirical findings also indicated that there is no significant trade-off relationship between inflation rate and marginal cost. In other words, there is no significant negative association between inflation rate and marginal cost.